Motor control in aerospace, optimizing availability and acoustics - Skoulaxinos, Stefanos (2024)
The objective of this research project was to investigate motor control methods applied to Permanent Magnet Synchronous Motors (PMSMs) for aerospace applications. In specific this research attempted to address two key issues that are critical in aerospace. Firstly the increase in system availability in case of a resolver failure by means of applying sensorless motor control methods. Secondly the reduction of acoustic noise generated from a motor drive. Reliability, availability and acoustics are key areas in a number of industries especially aerospace. With regards to the reliability and availability objective, a hybrid model/saliency based sensorless method was investigated that can take over motor control in case of a resolver failure.